Analysis the Expansion of Base Station’s Coverage for Gsm Cellular Network Using Solar Cell at Gadog Village, West Java, Indonesia - Pramono, Tri Joko; Husada, Hendrianto (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The presence of Global system for Mobile technology provides opportunities for the development of information and communication technology towards more valuable automation. One of the benefits that become the backbone to support today's communication activities is high-speed internet access which has reached the 4G version. However, this version upgrade is not necessarily evenly distributed in all regions in Indonesia, Gadog village located in the West Java ,Cianjur region is one area that can be called an isolated area from GSM telecommunication signals, this is due to the topology of the area which is between the hills. Therefore, a GSM signal amplification system is needed to support the use of GSM-based telecommunications and the use of the internet as a gateway for information exploration.